2022
DOI: 10.1075/sar.21014.li
|View full text |Cite
|
Sign up to set email alerts
|

Effects of linguistic proficiency on speech act development in L2 Chinese during study abroad

Abstract: This study investigated the effects of different levels of linguistic proficiency on the development of multiple speech acts during study abroad. Participants were 109 American learners of Chinese recruited from a study abroad program in China. They were divided into a higher proficiency (HP) group and a lower proficiency (LP) group based on their scores on a standardized Chinese proficiency test. The participants completed a computerized oral Discourse Completion Test (DCT) that assessed the production of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…Similarly, the results revealed that there was no statistically significant difference between the scores of the students who participated in the study from the General Pragmatic Motivation Questionnaire (GPMQ) according to their English level. While some studies suggest the influence of English proficiency level on students’ pragmatic Motivation (Li et al, 2022; Kieseier et al, 2022), our study found otherwise. These findings are insightful in guiding teachers in their classroom practices.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Similarly, the results revealed that there was no statistically significant difference between the scores of the students who participated in the study from the General Pragmatic Motivation Questionnaire (GPMQ) according to their English level. While some studies suggest the influence of English proficiency level on students’ pragmatic Motivation (Li et al, 2022; Kieseier et al, 2022), our study found otherwise. These findings are insightful in guiding teachers in their classroom practices.…”
Section: Discussioncontrasting
confidence: 97%
“…Knowledge of speech acts may help effective communication. Research shows that speech acts aid language cognitive processes (Li et al, 2022; M. F. Lin et al, 2022; Panahzadeh & Asadi, 2019; Sharqawi & Anthony, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is difficult to compare or generalize the findings from these studies, considering that they differ in languages studied, duration of time abroad, student profile, and even how they operationalized and measured pragmatic development. Different speech acts may even develop at different rates (Li et al, 2022;Taguchi, 2013). The common thread they share is their examination of the development of uninstructed students.…”
Section: This Issue)mentioning
confidence: 99%
“…The common thread they share is their examination of the development of uninstructed students. However, Shively (2010) warns that "uninstructed L2 learners typically make only minor gains in target-like pragmatic competence" (p. 106), bearing in mind that pragmatic development is dependent on a myriad of complex factors such as L2 proficiency (Barron, 2020;Li et al, 2022), social contact (Sánchez-Hernández & Alcón-Soler, 2019Taguchi et al, 2016), and identity (Liu et al, 2022;Masuda, 2011;Morris, 2017;Shively, 2011). Adding COVID to this list of factors only further muddies the waters.…”
Section: This Issue)mentioning
confidence: 99%
“…As regards the pragmatic moves analyzed, speech acts have been extensively investigated (Li et al 2022), as in many studies in interlanguage pragmatics (ILP), leaving other pragmatic aspects generally unexplored. This is the reason why the present study focuses on pragmatic markers (PMs), which have been mainly examined among adult learners (e.g., Magliacane and Howard 2019).…”
Section: Introductionmentioning
confidence: 99%